As veredas do bode : criação na solta e laboro no sertão de Pernambuco - Zambrini, Ariane Vasques (2016)
The goal on this dissertation performs both a description and an analysis on human and nonhuman relation based on Floresta's countryside, a town located in Pernambuco State. I have described this relation from some different point of view, yet their particular way of breeding (criação na solta) has been the main focus on my analysis. The intensive field research gave rise to the sketching of interspecies relations in that area. It had occurred in the period of three months when took place conversations and interviews with local husbandman who breeds both in the countryside (no mato) and the streets (na rua). In particular, the issue draws upon a description about how five families from the riparian zone (Cachoeira, Pocinhos, Quebra-Unha, Capim e Riacho do Meio) deal with and understand their relations with goats. At first, my analysis looks forward to the contrast between laboro as a husbandman daily activity and both the concept of work and and the extensive production method. The laboro is a set of very specific procedure and skill – a part of what is called criação na solta – and they are a condition of possibility for what I intend to describe and understand. Signs belong to the set of skills: they are a knife cutting made at the goat's ear which concurrently symbolize and identify the animal's owner and its family. The laboro and the signs are ways of realization and accomplishment of family affiliation. The laboro relies upon the animal's intense acquaintance with the caatinga which brings together a particular husbandry expertise; just a few men knows the terrain and how to breed goats. The concept of domestication can be drawn from the nexus relating breeder, livestock and caatinga in the manner of their mutual relation. Hence, from the standpoint of breeders and their families I describe how this practical way of breeding give rise to an understanding on interspecies relation in a given region. Those who knows the veredas, the goat-tracks traced as daily over the years, knows as well the ground pattern and footprint which deliver a way of being which is proper to husbandman, caatinga and the goat.